2021
DOI: 10.1186/s12863-021-00982-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of an extensively drug resistant (XDR) M. morganii SMM01 isolated from a patient with urinary and fecal incontinence

Abstract: Objective M. morganii is a gram-negative, non-lactose fermenting and an opportunistic pathogen frequently associated with nosocomial infections. Although first isolated in 1906 from a pediatric fecal sample, not many M. morganii isolates have been sequenced. The objective of this work is to determine the complete genome sequence of an XDR M. morganii strain (SMM01) isolated from the urine of a patient with urinary and fecal incontinence and to characterize its antimicrobial resistance profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…130 Similarly, for E. cloacae we found only two studies that reported the total of two whole genome sequences, while for M. morganii and K. aerogenes , we found one study with a single sequence each. 132135…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…130 Similarly, for E. cloacae we found only two studies that reported the total of two whole genome sequences, while for M. morganii and K. aerogenes , we found one study with a single sequence each. 132135…”
Section: Resultsmentioning
confidence: 99%
“…130 Similarly, for E. cloacae we found only two studies that reported the total of two whole genome sequences, while for M. morganii and K. aerogenes, we found one study with a single sequence each. [132][133][134][135] We also looked at the geographic distribution of the whole-genome sequences across the six different geo-climatic zones of India (Figure 2). Out of the 2547 sequences, we could locate the geo-climatic zones of 1653 sequences (64.90% of the sequences) based on the information in the reported study or from the NCBI metadata associated with the genomic sequence.…”
Section: Number Of Whole-genome Sequences For Any Selected Pathogen V...mentioning
confidence: 99%
See 1 more Smart Citation